2001
DOI: 10.1089/104454901753340613
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Novel Family of Mammalian Ependymin-Related Proteins (MERPs) in Hematopoietic, Nonhematopoietic, and Malignant Tissues

Abstract: Evidence is presented for a family of mammalian homologs of ependymin, which we have termed the mammalian ependymin-related proteins (MERPs). Ependymins are secreted glycoproteins that form the major component of the cerebrospinal fluid in many teleost fish. We have cloned the entire coding region of human MERP-1 and mapped the gene to chromosome 7p14.1 by fluorescence in situ hybridization. In addition, three human MERP pseudogenes were identified on chromosomes 8, 16, and X. We have also cloned the mouse MER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…2). This tissue distribution is consistent with that observed by Northern blot analysis (30). An additional band of ϳ32 kDa was also observed in two of the three skeletal muscles examined (see Fig.…”
Section: Resultssupporting
confidence: 90%
“…2). This tissue distribution is consistent with that observed by Northern blot analysis (30). An additional band of ϳ32 kDa was also observed in two of the three skeletal muscles examined (see Fig.…”
Section: Resultssupporting
confidence: 90%
“…The sequence analysis of the conceptual translation of the ependymin clone reveals 63% similarity (47% identity) with mammalian ependymin-related proteins MERP-1/upregulated in colon cancer 1 (UCC1) (accession no. AY027862 and AJ250475, respectively) (Apostolopoulos et al, 2001;Nimmrich et al, 2001), close relationship (30% similarity, 40% identity) with the frog X. laevis (accession no. BG553216.1) and 40 -46% similarity, 24 -32% identity with the piscine ependymins (Orti and Meyer, 1996).…”
Section: Identification and Sequence Analysis Of The Epenhg Genementioning
confidence: 99%
“…Examples of that similarity are the sequences perfectly conserved Q 36 WEGR 40 , and V 137 QEWSDR 143 , and the highly conserved R 66 VIEEKKSFMPGRRFYEYIMEYK 88 , and E 150 SWIGIYT 157 (numbers with reference to the EpenHg sequence). Previously, two consensus patterns that include all the ependymin proteins known from vertebrates (Apostolopoulos et al, 2001) were identified. By including the echinoderm sequences, we have updated the ependymin consensus pattern including all the vertebrate and the invertebrate sequences known so far:…”
Section: Alignment Comparison and Phylogeny Of Ependymin Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, orthologues of fish EPN, also exist in other animals such as sea urchin, frog, and even in mammals, and have been also named as EPDR (ependymin-related) protein or MERP (mammalian ependymin-related protein). Humans, in particular, have one isoform of EPN and its expression has been reported in various human normal tissues [8,9]. More interestingly, the transcription level of human EPN was elevated in colorectal tumor cells, and hence is also called UCC1 (upregulated in colorectal cancer gene 1) [10].…”
Section: Introductionmentioning
confidence: 99%